TEACHER AND STUDENT NEEDS ANALYSIS FOR DEVELOPING AN SDG 10-BASED BIG BOOK TO PROMOTE PRESCHOOL STUDENTS' BEHAVIORAL READING ENGAGEMENT - Kadek Citra Gotra Jaya; Luh Gd Rahayu Budiarta; Ni Wayan Monik Rismadewi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Behavioral reading engagement plays an important role in fostering preschool students' literacy experiences; however, its effectiveness is influenced by the suitability of the instructional media used during shared reading activities. This study was conducted to identify teachers' and students' needs as the basis for developing an SDG 10-based Big Book for English shared reading instruction. A qualitative descriptive approach was employed involving one English teacher and preschool students at Girikarnika Montessori Preschool, Bali. Data were collected through classroom observations and semi-structured interviews and subsequently analyzed using Braun and Clarke's thematic analysis. The findings indicate that although shared reading has successfully promoted students' attention, participation, and interaction, its effectiveness remains constrained by reading materials that are not fully aligned with the characteristics of preschool students and have yet to incorporate the values of equality, inclusion, and respect for diversity. These findings highlight the need to develop a Big Book featuring engaging illustrations, simple language, and contextually relevant stories that integrate SDG 10 values in order to sustain students' engagement throughout reading activities. Overall, this needs analysis provides an empirical foundation for the development of literacy media that not only enhances preschool students' behavioral reading engagement but also strengthens the integration of inclusive values into English learning from an early age. ABSTRAK Behavioral reading engagement menjadi salah satu aspek penting dalam membangun pengalaman literasi siswa prasekolah, namun keberhasilannya dipengaruhi oleh kesesuaian media yang digunakan selama kegiatan shared reading. Kondisi tersebut mendorong penelitian ini untuk mengidentifikasi kebutuhan guru dan siswa sebagai dasar pengembangan Big Book berbasis SDG 10 pada pembelajaran English shared reading. Penelitian menggunakan pendekatan deskriptif kualitatif yang melibatkan seorang guru English dan siswa prasekolah di Girikarnika Montessori Preschool, Bali. Data diperoleh melalui observasi kelas dan wawancara semi-terstruktur, kemudian dianalisis menggunakan analisis tematik Braun dan Clarke. Analisis menunjukkan bahwa pelaksanaan shared reading telah mampu mendorong perhatian, partisipasi, dan interaksi siswa, tetapi efektivitasnya masih dibatasi oleh media bacaan yang kurang sesuai dengan karakteristik siswa prasekolah serta belum mengintegrasikan nilai-nilai kesetaraan, inklusi, dan penghargaan terhadap keberagaman. Temuan tersebut mengindikasikan perlunya pengembangan Big Book dengan ilustrasi yang menarik, bahasa yang sederhana, serta cerita yang kontekstual dan memuat nilai-nilai SDG 10 agar keterlibatan siswa selama membaca dapat dipertahankan. Dengan demikian, analisis kebutuhan ini memberikan landasan empiris bagi pengembangan media literasi yang tidak hanya mendukung peningkatan behavioral reading engagement siswa prasekolah, tetapi juga memperkuat penanaman nilai-nilai inklusif dalam pembelajaran English sejak usia dini.